Nomenclatural and taxonomic notes in Phymatidium geiselii (Oncidiinae, Orchidaceae) - Toscano de Brito, Antonio L. V.; Royer, Carla Adriane; de Camargo Smidt, Eric (Lankesteriana: International Journal on Orchidology, 2016)
Phymatidium glaziovii is proposed as a new synonym for P. geiselii. A lectotype and an epitype are selected for P. geiselii. Illustrations and taxonomic discussions are also provided.